Heterogenization of marine catch assemblages over the past two decades in China - Zhiqi Zhang; Zhiyuan Ma; Tianjiao Feng (Environmental Research Communications)
The trajectories of marine catch assemblages in response to anthropogenic change at large temporal and spatial scales remain elusive, posing a threat to marine fishery biodiversity and food security. Here, we use data collected from the China Fishery Statistical Yearbook from 2003 to 2019 to systemically and quantitatively assess the trajectory change of marine catch assemblages and the drivers. Over the past two decades, we observed obvious temporal heterogenization in species taxa and structure for both occurrence and abundance-based dissimilarity in marine catch composition, with key fish species identified as the primary drivers, especially Thunnus albacares and Trachurus japonicus . The heterogeneity rate is particularly pronounced in low-latitude southern regions. While overall species richness remained relatively stable, these findings highlight the critical need to shift our conservation focus from biodiversity loss to composition change as a key indicator of marine ecosystem health. These findings can aid in the creation of sustainable marine conservation and fisheries management decisions to rebuild the resilience of marine fishery stocks.